Reduced female fertility due to sequestration of RNA Pol II by pervasive transcription in exosome RNase-depleted oocytes - Di Wu; Jurrien Dean (Cell Reports, 2023)
Summary: Perturbing the transcriptome of mammalian oocytes results in meiotic failure. We previously reported that RNA-exosome-associated RNase, EXOSC10, degrades unwanted protein-coding RNA and processes ribosomal RNA to ensure proper oocyte maturation. Here, we establish oocyte-specific knockout mice of another RNA-exosome-associated RNase, DIS3. Mutant females (Dis3cKO) exhibit significantly reduced fertility because oocytes arrest after the growth phase. Single-oocyte RNA sequencing (RNA-seq) and CUT&Tag analyses show that DIS3 degrades intergenic RNA and mediates transcription silencing that is essential for chromatin condensation and resumption of meiosis. Dis3cKO oocytes exhibit elevated H3K27me3 in a pre-defined manner due to insufficient demethylation. During oocyte growth, EXOSC10 functions with DIS3 to degrade intergenic RNA. Double-knockout oocytes have earlier growth defects and more accumulated transcripts. We conclude that RNA exosomes synergistically degrade unwanted RNA and mediate transcription termination to ensure transcriptome integrity during oocyte development.